2018
DOI: 10.14202/vetworld.2018.687-692
|View full text |Cite
|
Sign up to set email alerts
|

Improvising livestock service in hilly regions through indigenous wisdom towards control of tick infestation: Institutional relationships

Abstract: Aim:This study was conducted to demonstrate the acaricide efficacy of novel indigenous veterinary medication shared by an outstanding knowledge holder against naturally infested cattle and efforts in mainstreaming such wisdom.Materials and Methods:An indigenous herbal medication in control of tick infestation was documented, and experimentation was held against naturally affected cattle. Eighteen clinically infested cattle population comprising 16 crossbred and 2 non-descript cattle were purposively selected. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(34 reference statements)
1
0
0
Order By: Relevance
“…similar withKataviya et al (2018), who demonstrated the acaricidal e cacy of novel indigenous herbal veterinary medication in the control of tick infestation against naturally affected cattle and found reduction in the pre-treatment tick count without any reactions at the application site and healthier skin conditions post treatment. Bhikane et al (2018) also noticed signi cant reduction in clinical signs like itching, alopecia, redness, rubbing, pruritus and coarse skin coat with varying degrees of hair fall after treatment with polyherbal spray containing neem.…”
supporting
confidence: 73%
“…similar withKataviya et al (2018), who demonstrated the acaricidal e cacy of novel indigenous herbal veterinary medication in the control of tick infestation against naturally affected cattle and found reduction in the pre-treatment tick count without any reactions at the application site and healthier skin conditions post treatment. Bhikane et al (2018) also noticed signi cant reduction in clinical signs like itching, alopecia, redness, rubbing, pruritus and coarse skin coat with varying degrees of hair fall after treatment with polyherbal spray containing neem.…”
supporting
confidence: 73%